2021
DOI: 10.3389/fimmu.2021.627186
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Adequate T and B Cell Responses in a SARS-CoV-2 Infected Patient After Immune Checkpoint Inhibition

Abstract: After the COVID-19 outbreak, non-evidence based guidelines were published to advise clinicians on the adjustment of oncological treatment during this pandemic. As immune checkpoint inhibitors directly affect the immune system, concerns have arisen about the safety of immunotherapy during this pandemic. However, data on the immune response in oncology patients treated with immunotherapy are still lacking. Here, we present the adaptive immune response in a SARS-CoV-2 infected patient who was treated with immune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Indeed, the potential impact of ICIs as well as of other monoclonal antibodies used in endocrine patients such as denosumab [94]on the clinical outcome of COVID-19 has not been yet fully evaluated. However, a very recent case report demonstrated a sufficient cellular and humoral immune response in a SARS-CoV-2 infected patient who was on treatment with immune checkpoint inhibitors for advanced renal cell cancer, supporting the concept of not suspending ICIs during the ongoing COVID-19 pandemic [95].…”
Section: Hypophysitismentioning
confidence: 98%
“…Indeed, the potential impact of ICIs as well as of other monoclonal antibodies used in endocrine patients such as denosumab [94]on the clinical outcome of COVID-19 has not been yet fully evaluated. However, a very recent case report demonstrated a sufficient cellular and humoral immune response in a SARS-CoV-2 infected patient who was on treatment with immune checkpoint inhibitors for advanced renal cell cancer, supporting the concept of not suspending ICIs during the ongoing COVID-19 pandemic [95].…”
Section: Hypophysitismentioning
confidence: 98%
“…Numerous studies have suggested that COVID19 increases the risk of accelerated cancer progression, metastasis, and death in cancer patients in general and in breast cancer patients in particular ( 5 , 12 , 13 , 54 , 55 ). Indeed, our previous study reported the induced effects of the SARS-CoV-2 M-protein on the migratory ability and metastasis of BCC, suggesting that it promoted aggressiveness in BCC ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“… NA CRP↑ Paracetamol Improved and continue with the adjuvant treatment while delaying the next dose by 3 weeks 4 Arenbergerova et al [ 35 ] 59/M Czech NA Melanoma, stage IIIB Pembrolizumab, Q3W NA Fever, fatigue, dry cough. NA CRP↑ Paracetamol Improved and continue with the adjuvant treatment while delaying the next dose by 3 weeks 5 Artigas et al [ 36 ] 51/M Belgium NA Renal cell carcinoma Nivolumab NA Fatigue, anorexia Ground glass opacities in both lungs LDH: 365 U/L; lymphocyte: 1.16*10 3 /mm 3 ; CRP: 167 mg/L Hydroxychloroquine, piperacillin/tazobactam NA 6 de Joode et al [ 37 ] 62/M Netherlands Type 2 diabetes, hypertension Renal cell cancer with metastases Ipilimumab, nivolumab 42 Cough, dyspnea NA Lymphocytes↓ Prednisolone, cefuroxime, azithromycin Died 30 days after discharged due to severe neurological deterioration 7 Di Giacomo et al [ 38 ] 74/M Italy Renal cell carcinoma Metastatic cutaneous melanoma Anti-PD-1, 83 cycles 5 Fever, mild dyspnea, cough Bilateral pneumonitis CRP: 4.22 mg/liter; lymphocytes: 1060/mm 3 Azithromycin, darunavir/ritonavir, hydroxychloroquine, oxygen therapy Improved and resumed ICI treatment 8 Di Giacomo et al [ 38 ] 51/F Italy NA Melanoma, stage IV Anti-PD-1, 11 cycles 6 Asthenia, nausea, fever, headache NA CRP: 1.1 mg/liter; lymphocytes: 1105/mm 3 Self-isolation ...…”
Section: Clinical Characteristics Of Sars-cov-2 Infection In Cancer P...mentioning
confidence: 99%